“Somebody has to teach the ‘broccoli’ course”: Administrators Navigating Student Evaluations of Teaching (SET) - Vargas-Madriz, Luis Francisco; Nocente, Norma; Best-Bertwistle, Rebecca; Forgie, Sarah (Canadian Journal of Higher Education, 2019)
Student Evaluations of Teaching (SET) have been the most consistently administered tool, and they are still extensively used in higher education institutions to assess teaching effectiveness. The purpose of this study was to explore how SET are used by administrators in the teaching evaluation process at a large, research-intensive Canadian university. A basic qualitative research design was used in this project, and semi-structured interviews were used to obtain administrators’ experiences. The research question that guided this study was: How are SET (and other tools) used in the evaluation of teaching at this university? Findings showed that although participants mostly utilized a couple of SET statements as indicators of effective teaching, they were certainly aware of the intrinsic issues concerning these tools, and that they are continually seeking to obtain more evidence if SET results are below their benchmarks.